THE PHILOSOPHICAL ESSENCE OF THE PSYCHOANALYTICAL WORLD OUTLOOK. - Kinkel, Ivan (Bulgarian Philosophical Review / Bulgarski Filosofski Pregled, 2022)
The article sets forth some of the main ideas of the psychoanalytical teaching of Z. Freud. It emphasizes the dependence of mental powers and processes of man on the primary propulsive instinct in him. The author has stated that culturally and historically and from a sociological point of view the psychoanalytical teaching may be defined as society's readiness for self-analysis; it is its resolute desire to peer boldly into its own soul, by subjecting the instinct foundations of the soul, i.e. of the life of the individual and society to a psychological research. Psychoanalysis has been defined as the most successful attempt at understanding the hidden and mysterious aspect of the human soul. It drives human thought to the point that a return to the old idealistic illusions, veiling and concealment is no longer possible for man: he has finally matured, has abandoned the infantile psychology which has made him swing for centuries in the world of sweet fairytales about him, his specific nature and aristocratic standing in life.